Design of a Web-Based Mountain Equipment Rental Information System: A Case Study of Semeton Pendaki - Novaidi; Danang Tejo Kumoro; Ramadhana Agung Pratama (Breakthroughs In Informatics, Networking, Algorithms, Research, And Yield (BINARY), 2025)
This study presents the design of a web-based information system for mountain equipment rental at Semeton Pendaki, a local outdoor gear rental business located in Narmada. The current manual rental process has led to various inefficiencies, including limited customer access to equipment availability and slow transaction management. To address these issues, a web-based platform was developed using the System Development Life Cycle (SDLC) with the Waterfall model. The system was implemented using PHP with Laravel framework, VueJS for frontend development, and MySQL for database management. Data collection techniques included observation, interviews with stakeholders, and literature review. The system features include real-time catalog access, online booking, transaction tracking, inventory management, and administrative reporting. System testing was conducted using the black-box method to ensure that each function worked according to specifications. The results indicate that the developed system improves the efficiency and transparency of the rental process. Customers can access the catalog and place orders without visiting the rental location, while administrators benefit from structured transaction records and automated reporting. This system not only enhances user experience but also supports operational competitiveness in an increasingly digital market. The study suggests future enhancements such as integration of online payments, mobile responsiveness, and user data security